Violence as worship: religious wars in the age of globalization - Kippenberg, Hans Gerhard (Stanford University Press, 2011)
Violent religious practices -- The growth of social communities in the age of globalization -- Faith communities as actors in civil society -- The People's Temple -- Every day Ashura, every tomb Kerbala : Iran 1977-1981 -- "The party of God" intervenes in the war : Lebanon 1975-2000 -- Israel's wars of redemption -- Fighting for the foundational land (waqf) of Palestine -- American Protestants prepare the way for the eschatological battlefield in Palestine -- September 11, 2001 : a raid (ghazwa) on the path of God -- The war of the USA against terror, a war without borders -- Concluding remarks : wars of religion in the age of globalization